Quality of life in patients with non-small cell lung cancer - Šarac, Sanja B.; Milić, Rade; Vasiljević, Mira; Šarac, Momir (Vojnosanitetski pregled, 2017)
Background/Aim. As lung cancer is considered the greatest contributor to death among all cancer types any help might be valuable in the assessment of treatment effects. The aim of this study was for assess the quality of life (QoL) in patients with non-small cell lung cancer (NSCLC) treated with gemcitabine-cisplatin regimen as the first line of chemotherapy. Methods. The QoL was assessed using certified Serbian translations of the European Organization for Research and Treatment of Cancer Quality Life Questionnaire Core 30 (EORTC QLQ-C30) and Lung Cancer Module (QLQ-LC13) – version 3. The questionnaire was used before starting treatment and after the completion of the 2nd and the 4th cycle of chemotherapy. The questionnaire scales and single items were compared in order to assess the impact of treatment on the QoL. Results. A total of 60 patients started and 51 completed all questionnaires. There were no changes in the global health status score between the baseline, the 2nd and the 4th cycle of chemotherapy (42.78 ± 15.76, 45.56 ± 17.59, 48.20 ± 19.24, respectively; p = 0.1). Social function score, symptom scores: nausea and vomiting, pain, appetite loss, constipation, diarrhea and financial difficulties score differed significantly among chemotherapy cycles, indicating improved or worsened the QoL. In the lung cancer symptom score a significant difference between measurements was observed in cough, alopecia, chest pain and in using analgesics. Conclusion. Monitoring of changes in the QoL among patients with locally advanced and metastatic NSCLC showed that chemotherapy did not decrease the global health status but led to significant changes in the social and financial functioning of patients. Some symptoms associated with the disease reduced in the intensity but some new occurred as a result of chemotherapy. Using questionnaires to assess the QoL helped in easier identification of adverse effects and specific problems for adequate treatment.
Keywords: quality of life; carcinoma; non-small-cell lung; antineoplastic combined chemotherapy protocols; surveys and questionnaires